206k views
1 vote
Expand the polynomial. 1. (m^2-n)(m^2+2n^2)2. (a-2)(4a^3-3a^2)

User Tauseef
by
5.6k points

1 Answer

4 votes

1)

The given polynomial is


(m^2-n)(m^2+2n^2)

Multiply as follows:


(m^2-n)(m^2+2n^2)=m^2(m^2+2n^2)-n(m^2+2n^2)


=m^2* m^2+m^2*2n^2-n* m^2-n*2n^2


=m^4+2m^2n^2-m^2n-2n^3

Hence the required expansion is


(m^2-n)(m^2+2n^2)=m^4+2m^2n^2-m^2n-2n^3

2)

The given polynomial is


(a-2)(4a^3-3a^2)

Multiply as follows:


(a-2)(4a^3-3a^2)=a(4a^3-3a^2)-2(4a^3-3a^2)


=a*4a^3-a*3a^2-2*4a^3-(-2)*3a^2


=4a^4-3a^3-8a^3+6a^2


=4a^4-11a^3+6a^2

Hence the required expansion is


(a-2)(4a^3-3a^2)=4a^4-11a^3+6a^2

User Kitap Mitap
by
6.1k points